Mucosal IgA Prevents Commensal Candida albicans Dysbiosis in the Oral Cavity - Millet, Nicolas; Solis, Norma V.; Swidergall, Marc (Frontiers in Immunology, 2020)
The fungus Candida albicans colonizes the oral mucosal surface of 30-70% of healthy individuals. Due to local or systemic immunosuppression, this commensal fungus is able to proliferate resulting in oral disease, called oropharyngeal candidiasis (OPC). However, in healthy individuals C. albicans causes no harm. Unlike humans mice do not host C. albicans in their mycobiome. Thus, oral fungal challenge generates an acute immune response in a naive host. Therefore, we utilized C. albicans clinical isolates which are able to persist in the oral cavity without causing disease to analyze adaptive responses to oral fungal commensalism. We performed RNA sequencing to determine the transcriptional host response landscape during C. albicans colonization. Pathway analysis revealed an upregulation of adaptive host responses due to C. albicans oral persistence, including the upregulation of the immune network for IgA production. Fungal colonization increased cross-specific IgA levels in the saliva and the tongue, and IgA+ cells migrated to foci of fungal colonization. Binding of IgA prevented fungal epithelial adhesion and invasion resulting in a dampened proinflammatory epithelial response. Besides CD19+ CD138- B cells, plasmablasts, and plasma cells were enriched in the tongue of mice colonized with C. albicans suggesting a potential role of B lymphocytes during oral fungal colonization. B-cell deficiency increased the oral fungal load without causing severe OPC. Thus, in the oral cavity B lymphocytes contribute to control commensal C. albicans carriage by secreting IgA at foci of colonization thereby preventing fungal dysbiosis